Corticotropin‐releasing hormone‐binding protein is up‐regulated by brain‐derived neurotrophic factor and is secreted in an activity‐dependent manner in rat cerebral cortical neurons. Issue 1 (10th April 2018) - Adachi, Naoki; Suzuki, Shingo; Matsuoka, Hidetada; Fushimi, Satoko; Ono, Junichiro; Ohta, Ken‐ichi; Hirai, Yohei; Miki, Takanori; Koshimizu, Hisatsugu
Abstract: A recent study revealed that corticotropin‐releasing hormone (CRH) in the cerebral cortex (CTX) plays a regulatory role in emotional behaviors in rodents. Given the functional interaction between brain‐derived neurotrophic factor (BDNF) and the CRH‐signaling pathway in the hypothalamic‐pituitary‐adrenal axis, we hypothesized that BDNF may regulate gene expression of CRH and its related molecules in the CTX. Findings of real‐time quantitative PCR (RT‐qPCR) indicated that stimulation of cultured rat cortical neurons with BDNF led to marked elevations in the mRNA levels of CRH and CRH‐binding protein (CRH‐BP). The BDNF‐induced up‐regulation of CRH‐BP mRNA was attenuated by inhibitors of tropomyosin related kinase (Trk) and MEK, but not by an inhibitor for PI3K and Phospholipase C gamma (PLCγ). The up‐regulation was partially blocked by an inhibitor of lysine‐specific demethylase (KDM) 6B. Fluorescent imaging identified the vesicular pattern of pH‐sensitive green fluorescent protein‐fused CRH‐BP (CRH‐BP‐pHluorin), which co‐localized with mCherry‐tagged BDNF in cortical neurons. In addition, live‐cell imaging detected drastic increases of pHluorin fluorescence in neurites upon membrane depolarization. Finally, we confirmed that tetrodotoxin partially attenuated the BDNF‐induced up‐regulation of CRH‐BP mRNA, but not that of the protein. These observations indicate the following: In cortical neurons, BDNF led to gene expression of CRH‐BP and CRH. TrkB, MEK, presumably ERK, and KDM6B are involved in the BDNF‐induced gene expression of CRH‐BP, and BDNF is able to induce the up‐regulation in a neuronal activity‐independent manner. It is suggested that CRH‐BP is stored into BDNF‐containing secretory granules in cortical neurons, and is secreted in response to membrane depolarization. Abstract : The corticotropin‐releasing hormone (CRH)‐signaling pathway has received considerable attention for its biological functions in the cerebral cortex, while the regulation of gene expression of its related molecules in cortical neurons remains largely unknown. Here, we assessed whether and how brain‐derived neurotrophic factor (BDNF) regulates the gene expression of CRH‐binding protein (CRH‐BP) in cultured rat cortical neurons, and how CRH‐BP is secreted from cortical neurons. We indicated that BDNF induced the CRH‐BP gene expression in a TrkB‐, MEK‐, presumably ERK‐, and KDM6B‐dependent manner, and that CRH‐BP may be stored into BDNF‐containing granules and secreted in an activity‐dependent manner.